Chayote, Sechium edule (Swartz.) Propagation by Vine Cutting - Sharma, MD (Journal of the Institute of Agriculture and Animal Science, 2005)
Two experiments were conducted to determine the suitable mother vine and month for producing cutplants of chayote through vine cuttings. The survivals of young matured vine cuttings were greater (35- 87%) than those of old basal vine cuttings (26.3-64.3%) in all planting dates. In October planting, 53-75% cuttings survived 16 days. In November planting, 93% of the cuttings with 500 ppm IBA survived, of which 63% produced roots, while only 28% cuttings rooted in control. The survival pecent of vine cuttings planted in October, December and January were 75-87 and 100, respectively but none of them produced roots. Hence, November with mild temperature and high humidity was the best month for the production of cut-plants in chayote through vine cuttings under Chitwan condition. Key words: Chayote, vine cuttings, propagation, IBA J. Inst. Agric. Anim. Sci. 26:159-161 (2005)